1986
DOI: 10.1016/s0022-5347(17)45853-8
|View full text |Cite
|
Sign up to set email alerts
|

Skene’s Gland Calculi Produced by a Ureaplasma Urealyticum Infection

Abstract: We report a case of calculi in a Skene's gland abscess produced by Ureaplasma urealyticum. The enzyme urease, produced by the Ureaplasma urealyticum, is thought to be the etiological factor in stone production, vaginitis and urethritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…Experimental studies have shown that inoculation of U. urealyticum into rat bladders resulted in the formation of struvite stones and that U. urealyticum is capable of causing damage to the urothelial mucous coat, thus, promoting retention of struvite crystals [17, 18]. U. urealyticum can also act similarly in ducts and prostate tissue causing the formation of extensive calcifications, as anecdotally described in the Skene’s gland [19]. Prostate calcifications are a substrate that promotes the formation of biofilms in which the growth of other chronic prostatitis pathogens can be promoted [20].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have shown that inoculation of U. urealyticum into rat bladders resulted in the formation of struvite stones and that U. urealyticum is capable of causing damage to the urothelial mucous coat, thus, promoting retention of struvite crystals [17, 18]. U. urealyticum can also act similarly in ducts and prostate tissue causing the formation of extensive calcifications, as anecdotally described in the Skene’s gland [19]. Prostate calcifications are a substrate that promotes the formation of biofilms in which the growth of other chronic prostatitis pathogens can be promoted [20].…”
Section: Discussionmentioning
confidence: 99%
“…В умовах сьогодення представлено результати чисельних досліджень щодо формування простатиту у жінок, в етіологічному спектрі яких переважають інфекції, що передаються статевим шляхом [23,24,25,26,27,28,29,30,31,32,33]. Спектр представлених вище досліджень базувався на результатах клінічних спостережень Huffman J.W., який розширив уявлення про наявність можливих патологічних змін з боку жіночої передміхурової залози за умови формування запального процесу.…”
unclassified